Luminescent kinetic characteristics of CsPbCl₃ aggregates dispersed in Rb₁−xCsxCl (x = 0.05 ÷ 0.2) matrices - Myagkota, S.; Gloskovskii, A.; Gladyshevskii, R.; Voloshinovskii, A. (Condensed Matter Physics, 2003)
The luminescent kinetic parameters of the CsPbCl₃ nanocrystals dispersed in matrices of solid solutions Rb₁−xCsxCl (x = 0.05÷0.2) were studied under pulse synchrotron radiation excitation. Formation of CsPbCl₃ nanocrystals is confirmed by manifestation of the quantum size effect, which is displayed by a short-wave shift of the exciton luminescence maximum and an essential shortening of the luminescence decay time for of CsPbCl₃ nanocrystals as compared to that for an excitonic luminescence of a bulk single crystal CsPbCl₃. For the first time, using the atomic force microscopy method, the lead-containing nanocrystals embedded in a matrix of the Rb₀.₉₅Cs₀.₀₅Cl solid solution have been directly observed. Досліджено люмінесцентно-кінетичні параметри нанокристалів CsPbCl₃, диспергованих в матрицях твердих розчинів Rb₁−xCsxCl (x = 0.05÷0.2). Утворення нанокристалів CsPbCl₃ підтверджується проявом квантово-розмірного ефекту, який реалізується в короткохвильовому зсуві максимума випромінювання екситонної люмінесценції і суттєвому скороченні часу загасання люмінесценції нанокристалів по відношенні до такого, характерного для смуги екситонної люмінесценції об’ємного монокристала CsPbCl₃ . Вперше з використанням методу атомно-силової мікроскопії здійснено пряме спостереження свинцевовмісних нанокристалів, вбудованих у матрицю кристалічного розчину Rb₀.₉₅Cs₀.₀₅Cl.